Decomposing Migrant Self-Selection: Education, Occupation, and Unobserved Abilities - Ilpo Kauppinen; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2023)
We analyze self-selection and sorting of emigrants from Finland, using full-population administrative data from Statistics Finland. We analyze emigration events lasting at least five years and decompose migrant self-selection into education, occupation, and unobserved abilities. Our analysis focuses on Finnish citizens satisfying three criteria: they were between 25-54 years of age; they had no immigrant background; and they were employed. We find that emigrants from Finland are strongly positively self-selected in terms of education and earnings. We also find strong evidence of sorting: men who emigrate outside Nordic countries are considerably better educated and have higher earnings and residual earning than men who emigrate to Nordic countries. Most of the self-selection in terms of higher earnings can be explained by emigrants being more educated. Adding occupational controls increases the fraction of explained self-selection only marginally. While men are positively self-selected also with respect to residual earnings, women are not.
Keywords: F22; I26; J31; 330; international migration; self-selection; Roy model; education; residual earnings